Beethoven's Symphony no. 9 - Rehding, Alexander (Oxford keynotes., 2018)
"Beethoven's Ninth Symphony has held musical audiences captive for close to two centuries. Few other musical works hold such a prominent place in the collective imagination; each generation rediscovers the work for itself and makes it its own. Honing in on the significance of the symphony in contemporary culture, this book establishes a dialog between Beethoven's world and ours, marked by the earthshattering events of 1789 and of 1989. In particular, this book outlines what is special about the Ninth in millennial culture. In the present day, music is encoded not only as score but also as digital technology. We encounter Beethoven 9 flashmobs, digitally reconstructed concert halls, globally synchronized performances, and other time-bending procedures. The digital artwork 9 Beet Stretch even presents the Ninth at glacial speed over twenty-four hours, challenges our understanding of the symphony, and encourages us to confront the temporal dimension of Beethoven's music. In the digital age, the Ninth emerges as a musical work that is recomposed and reshaped-and that is robust enough to live up to such treatment-continually adapting to a changing world with changing media."--Provided by publisher